Wide-band gap device based battery charger - Muhammad Sharizad bin Safiee (Nanyang Technological University, 2023)
Wide-Band Gap devices, such as Silicon Carbide (SiC) and Gallium Nitride (GaN), have emerged as promising alternatives to traditional power semiconductors for high-performance and energy-efficient power conversion applications. This study focuses on the use of WBG devices in battery chargers, which plays an important role in ensuring safe and efficient charging of batteries. The study investigates the design and implementation of WBG-based battery charger circuits, including topologies such as buck, boost, and buck-boost. The assessment and comparison of the performance of WBG devices with conventional power semiconductors, such as MOSFETs, are conducted. This study also explores the implementation of control algorithms, voltage and current regulation, to ensure safe and efficient battery charging. The thermal performance of the WBG-based battery chargers is also investigated, and the compatibility of these chargers with different types of batteries, including lithium-ion, lead-acid, and NiMH, is evaluated. The study aims to provide insights into the benefits and challenges of using WBG devices in battery chargers, and to demonstrate the potential for WBG-based battery chargers to improve the performance and efficiency of battery charging systems. In conclusion, this study provides a comprehensive analysis of the design and performance of WBG-based battery chargers, and highlights the potential benefits of using WBG devices in these chargers. The findings of this research could potentially provide valuable insights for the advancement of battery charging systems that are both high-performing and energy-efficient.